Comparing and Correlating Outcomes between Open and Percutaneous Access in Endovascular Aneurysm Repair in Aortic Aneurysms Using a Retrospective Cohort Study Design. (29th November 2020) - DeVito, Peter; Kimyaghalam, Ali; Shoukry, Sameh; DeVito, Robert; Williams, John; Kumar, Eashaa; Vitvitsky, Eugene
Abstract : Objective . This retrospective cohort study is aimed at determining the safety and efficacy between Femoral Open-Cutdown access and Percutaneous access with Endovascular Aneurysm Repair (EVAR) by contrasting perioperative complication rates. We hypothesized that the percutaneous approach is a better alternative for aortic aneurysm patients as it is minimally invasive and has been demonstrated to decrease the length of hospital stay. Methods . We retrospectively reviewed data for patients undergoing EVAR between the years of 2005 and 2013. We then compared overall mortality, hematoma or seroma formation, graft infection, arterio-venous injury, distal embolization, limb loss, myocardial infarction or arrhythmia, and renal dysfunction. Results were demonstrated using a retrospective cohort study design to confirm the hematoma rate associated with EVAR open compared to percutaneous access. Results . Our series involves 73 patients who underwent percutaneous access for EVAR (n = 49 ) or traditional open cutdown (n = 24 ). Percutaneous access resulted in significantly less hematoma formation when compared to the traditional open cutdown (4% vs. 12.5%; p < 0.059 ). Our analysis suggests decreased mortality rates associated with EVAR as compared to the Open-Cutdown method using Northside Medical Center's Study and the OVER Veterans Affairs Cooperative Study (p = 0.0053 ). Conclusion . Percutaneous access for EVAR is safe and effective when compared to Open-Cutdown access for aortic aneurysm patients. Percutaneous access was associated with decreased rates of in-hospital mortality, hematoma formation, graft infection, and respiratory failure.